Profile of at-risk newborns attended by nurses in outpatient follow-up clinic: a retrospective cohort study - Ludmylla de Oliviera Beleza; Laiane Medeiros Ribeiro; Rayanne Augusta Parente Paula; Laíse Escalianti Del Alamo Guarda; Gessica Borges Vieira; Kassandra Silva Falcão Costa (Universidade de São Paulo, 2019)
ABSTRACT Objective: to analyze the cohort profile of at-risk newborns attended by nurses in a multidisciplinary follow-up clinic, with emphasis on the type of feeding and weight gain, after hospital discharge. Method: retrospective cohort, whose population is composed of at-risk newborns attended in a 4-year period. Data came from medical records and attendance report, later exported to R Program. The outcome variables were number of the nursing consultation, type of feeding, daily weight gain and main guidelines. We used descriptive statistics, frequency distribution and applied Mann-Whitney, Chi-Square, Spearman correlation, Variance and Tukey analysis, with p <0.05 being significant. Results: a total of 882 consultations with 629 infants and families were analyzed. The frequencies of exclusive breastfeeding and weight gain increased as the consultations progressed. The infants who needed more consultations and with lower weight gain were those with lower gestational age (p = 0.001) and birth weight (p = 0.000), longer length of hospital stay (p <0.005), and diagnoses related to extreme prematurity (p <0.05), among others. Conclusion: nurses verified the importance of outpatient follow-up of at-risk newborns, especially in promoting breastfeeding and healthy growth.